PTMs in Conversation: Activity and Function of Deubiquitinating Enzymes Regulated via Post-Translational Modifications - Kessler, B; Edelmann, M (2011)
Deubiquitinating enzymes (DUBs) constitute a diverse protein family and their impact on numerous biological and pathological processes has now been widely appreciated. Many DUB functions have to be tightly controlled within the cell, and this can be achieved in several ways, such as substrate-induced conformational changes, binding to adaptor proteins, proteolytic cleavage, and post-translational modifications (PTMs). This review is focused on the role of PTMs including monoubiquitination, sumoylation, acetylation, and phosphorylation as characterized and putative regulative factors of DUB function. Although this aspect of DUB functionality has not been yet thoroughly studied, PTMs represent a versatile and reversible method of controlling the role of DUBs in biological processes. In several cases PTMs might constitute a feedback mechanism insuring proper functioning of the ubiquitin proteasome system and other DUB-related pathways. © 2011 The Author(s).